PELATIHAN PEMANFAATAN TEKNOLOGI INFORMASI MENGGUNAKAN MICROSOFT OFFICE WORD BAGI PERANGKAT DESA KRAKITAN, BAYAT, KLATEN - Sulistyowati, Istri; Retnowati, Niken; Kusuma, I Wayan Angga Wijaya; Kusumadewi, Afriliana; Windarti, Mariana (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2024)
This service aims to provide training to Krakitan village officials about the importance of information technology (one of which is Office Word) to support the performance of village officials in carrying out daily tasks serving village communities and to improve the quality of human resource performance, especially village officials in managing village administration activities. The activity method is carried out through direct training and practice. In this training, a basic introduction to computer use is provided, and training uses the Microsoft Word 2010 application. Then, case studies are provided for participants to complete. Next, an evaluation is carried out to determine the participant's level of ability after participating in the training activities. From the results of the activity, it was concluded that the training participants gave a positive response and were enthusiastic about participating in the activity from start to finish. The evaluation results also showed an increase in participants' abilities in operating Office Word as measured by the case studies given to participants which were completed well.